ANALISIS KESALAHAN DALAM PENERJEMAHAN TEKS BAHASA INGGRIS-BAHASA INDONESIA - Halim Shanty; A.R Bustamin (Institut Agama Islam Negeri Palopo, 2016)
The purpose of this research is to give a description about translating English sentence into Indonesian and arranging the phrase, clause or sentence structures by the students that may result a number of problems in their translations. The study is done by taking 20 students? translations of several sentences from one of the textbook of Civil Engineering in which the writers find that the students make many mistakes. These translations are analyzed and described by using a certain method of analysis. In this analysis the writers describe two linguistic aspects; lexical and grammatical aspects. The writers also describe the factors affected the students when making many errors in their translations. The study reveals that the students? way of translating the sentences result in a number of problems such as some mistakes/deviations in the selection of parable words in bahasa Indonesia, the arrangement of phrase and clause structure that affecting the translation of grammatical structure, the way of the students translate that is very literal, the lack of vocabulary, the lack translating experience and the lack translating theory and application.